Synthesis and characterization of microwave‐assisted biologically active triazole silanes. (5th March 2019) - Singh, Gurjaspreet; Satija, Pinky; Singh, Akshpreet; Sanchita,; Aulakh, Darpandeep; Wriedt, Mario; Ruiz, Cristobal Espinosa; Esteban, M. Angeles; Sinha, Shweta; Sehgal, Rakesh
Abstract : The alliance of new drug, green technology and public health initiatives is essential for the ecosystem. The microwave technique is used to synthesize new drugs cognate to metronidazole. A new family of triethoxysilanes (3a–3e ) was synthesized after reconnaissance with terminal alkynes (2a–2e ) as an array using the Huisgen 1, 3‐dipolar cycloaddition. All products were obtained in excellent yield with recovery of the catalyst as well as the solvent, and in a short time span. The design feature of these compounds is the tailoring of two unsymmetrical triazole nuclei into a single scaffold. The pharmacokinetic profiles of the triazole scaffold were analyzed using MOLINSPIRATION and ADMET toolkits, which gave promising results that prompted the investigation of these compounds for anti‐parasitic activity against parasites ( Giardia lamblia and Trichomonas vaginalis ) in contrast to standard drug (metronidazole). Compound3d manifested good efficacy against both strains amongst all the synthesized triazole analogs. Highlights: By using microwave methodology, a series of triazole functionalized alkynes and triazole organo silanes were synthesized. This involves tailoring of the 1, 2, 4‐triazole nucleus to 1, 2, 3‐triazole moiety. The protocol afforded excellent yield in a short time span under eco‐friendly conditions. The hybrid molecules were screened for their physicochemical properties using MOLINSPIRATION software and ADMET web server. All the synthesized compounds were investigated for their antioxidant activity, anti‐giardial and anti‐trichomonal activities. Tris triazole silane (3d ) was found to be the most significant against Giardia lamblia and Trichomonas vaginalis, respectively, and this low‐price, versatile drug will hopefully lead to the eventual elimination of parasitic disease from the human population. Thermal gravimetric analysis has been performed for compounds (2a–2e ) and (3a–3e ). Abstract : The present work articulates the synthesis of a new family of triethoxysilanes (3a–3e ) via microwave methodology. The beauty of the designed compounds is the tailoring of two unsymmetrical triazole nuclei into a single scaffold. The consolidated spectroscopy such as IR, NMR ( 1 H, 13 C, 29 Si), thermal gravimetric analysis used for characterization of compounds, corroborate by X ray diffraction studies for2a, 2b, 2e and mass spectrometry.